Il pensiero critico fra geografia e scienza del territorio Scritti su Massimo Quaini - Rossi, Luisa; CEVASCO, Roberta; Gemignani, Carlo Alberto; Poli, Daniela (Territori, 2021)
Massimo Quaini (1941-2017) was one of the most eminent figures in geography. A group of scholars dedicate this book to him in order to keep unwinding, in the world's labyrinth, the thread of his reflections, that placed geography among territorial sciences making them object of civil commitment. His critical, transdisciplinary thinking did never recognize boundaries but only fruitful differences of perspective: his highest legacy, perhaps, lays in this impulse to integrate different skills (of historians, poets, archaeologists, ecologists, planners...) to return the world's places their value. This is therefore not a typical 'in memoriam' book on Quaini's topics but, as we dare say, a book with Quaini.